Praktik Pemanfaatan Manajemen Aset Tetap pada Badan Pengelola Keuangan dan Aset Daerah Kota Malang - Adisya Safira Putri; Novrida Qudsi Lutfillah; Sidik Asmanu (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2020)
The aim of this study was to determine the utilization practice of regional fixed assets management at BPKAD (Financial and Regional Asset Management Body) of Malang City. This study used a qualitative design. The method of collecting data used was by interview, documentation, and observation. The results of the study showed that BPKAD used the utilization practice of fixed assets management or asset governance using SIMBADA in its registration. In practice, the utilization of fixed assets management encountered the problems namely many fixed assets are damaged because over economic age, in the legal foundation utilization is not optimized, and use of fixed assets have been maximized by regional work unit. Moreover, confusion of accessing computers in recording transaction by human resources cause incorrect record and budgeting.